Disturbances in the Glutathione/Ophthalmate Redox Buffer System in the Woodchuck Model of Hepatitis Virus-Induced Hepatocellular Carcinoma. (18th September 2011) - Andres Ibarra, Rafael; Abbas, R.; Kombu, R. S.; Zhang, Guo-Fang; Jacobs, G.; Lee, Z.; Brunengraber, H.; Sanabria, J. R.
Abstract : Purpose . The incidence of liver tumors is rising in USA. The purpose of this study was to evaluate liver oxido-reductive status in the presence of chronic liver disease and hepatocellular carcinoma (HCC). Methods . Glutathione species and ophthalmate (OA) concentrations were measured by LC-MS in processed plasma and red blood cells (RBC) from infected Woodchuck with hepatitis virus (WHV). Blood samples were obtained from: (i) infected animals with tumors (WHV+/HCC+), (ii) infected animals without tumors (WHV+/HCC−) and (iii) healthy animals (WHC−/HCC−). Results . The concentration of reduced glutathione (GSH) and the ratio GSH/GSG were lower in plasma from WHV+/HCC+ animals when compared to WHV+/HCC− and WHV−/HCC− (P < 0.01 ). In contrast, the concentration of oxidized glutathione (GSSG) was found to be higher in plasma from WHV+/HCC+ animals when compared to WHV+/HCC− and WHV−/HCC− (P < 0.01 ). The Glutathione species and its ratio from the RBC compartment were similar among all groups. OA concentration in both plasma and RBC was significantly higher from WHV+/HCC+ when compared to WHV+/HCC− and WHV−/HCC− (P < 0.01 ). Conclusions . Disturbances of the glutathione redox buffer system and higher concentrations of OA were found in the WCV+/HCC+ animal model. The role of these compounds as biomarkers of early tumor development in patients with end stage liver disease remains to be determined.